Results Of Using Html5 Language In Creating Web Platforms In Digital Educational Environments - Adilbay Kenesbayev (Periodica Journal, 2025)
This article highlights the possibilities of creating interactive web platforms through the effective use of HTML5 technology in the digital educational environment. The article analyzes the main capabilities of HTML5, the role of platforms created through it in education, and the conveniences and advantages of HTML5 based on examples.
Keywords: digital education; HTML5; CSS3